2020
DOI: 10.1111/1365-2435.13664
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of plant root responses to nutrient concentration, soil volume and neighbour presence: Different statistical approaches reflect different underlying basic questions

Abstract: To investigate the responses of plants to their below‐ground neighbours independently of nutrient availability, experiments generally require a solitary treatment with one plant grown alone with one unit of nutrients, and a neighbour treatment with two plants grown together with two units of nutrients. This can either be done by doubling nutrient concentration (C) or by doubling soil volume (V) in the neighbour treatment as compared to the solitary treatment. Statistically analysing the same dataset from an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Moreover, due to intrinsic differences in the mobility of different chemicals ( Raynaud and Leadley 2004 ), mesh-divided plants are more likely to compete for mobile resources, particularly water and nitrate, but not for less mobile ones, such as phosphate ( Chen et al 2020 ). Based on an assumption that root growth is mainly determined by nutrient concentration in local space, a simulation model showed that plants favour a much lower degree of root overlap with neighbours when competing for mobile nitrogen than when competing for immobile phosphorus ( de Vries 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, due to intrinsic differences in the mobility of different chemicals ( Raynaud and Leadley 2004 ), mesh-divided plants are more likely to compete for mobile resources, particularly water and nitrate, but not for less mobile ones, such as phosphate ( Chen et al 2020 ). Based on an assumption that root growth is mainly determined by nutrient concentration in local space, a simulation model showed that plants favour a much lower degree of root overlap with neighbours when competing for mobile nitrogen than when competing for immobile phosphorus ( de Vries 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the mesh allowed water, nutrients and even allelochemicals diffuse and pass through, it is safe to say that the exchange of root exudates, thus chemical communication including neighbour detection, can occur between mesh-divided soybean plants. Although the incentive for a TOC response predicted by game theory can be simply attributed to a balance between cost and benefit for root investment of a plant in response to the decline of soil nutrient concentration ( McNickle and Dybzinski 2013 ) but not to the presence of a neighbour per se , such a prediction has still been adopted as a reasonable hypothesis for testing the effects of neighbour detection ( Chen et al 2020 ). This is because, from an evolutionary perspective the ability of neighbour detection should facilitate plants to accurately compete for soil resources with neighbours rather than with themselves ( Chen et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work in this regard showed that plant roots can distinguish whether roots, with which they come in contact, are from the same plant or from a different plant (non‐self) (e.g., Chen, Vermeulen, During, & Anten, 2015; Gersani, Brown, O'Brien, Maina, & Abramsky, 2001; Gruntman & Novoplansky, 2004; Holzapfel & Alpert, 2003). While their methodology was criticized (e.g., Chen et al, 2015; Chen et al, 2020; Hess & de Kroon, 2007; McNickle, 2020; Semchenko, Hutchings, & John, 2007), it clearly spurred a wave of interest in identity recognition at the root level.…”
Section: Belowground Kin Recognition and Competition For Available Rementioning
confidence: 99%
“…However, it should be noted that the collected root exudates solutions (from, e.g., soil extracts, leachates or hydroponic medium) from different genotypes, families or varieties of plants may differ not only in the chemical composition of exudates which are supposedly involved in kin recognition but also in the composition and concentration of other compounds such as nutrients. Thus, we suggest that an adjustment of nutrient contents, at least the key elements N and P (Palmer et al, 2016), should be made for the collection of exudate solutions before treating focal plants with these solutions (Chen et al, 2020; Semchenko et al, 2014).…”
Section: Critical Considerations About Current Researchmentioning
confidence: 99%